(sorry if it's too late and you've already figured it out, but here you go anyway)
The easiest way to do this is to start by FOILing then add.
So just start with (x-1)(x-1)
(x-1)(x-1)
Front: (x*x) = x^2
Outer: (x*-1) = -x
inner: (-1*x) = -x
Last: (-1*-1) = 1
Added: x^2 -2x +1
Now take that answer and do the same thing with (x-1). It's basically the same thing, just with an added thing you need to multiply.
(x-1)(x^2-2x+1)
(x*x^2) = x^3
(x*2x) = 2x^2
(x*1) = x
(-1*x^2) = -x^2
(-1*-2x) = 2x
(-1*1) = -1
Now add everything together:
x^3+2x^2+x-x^2+2x-1
The answer is:
x^3+x^2+3x-1
Answer:
The answer world be 3.
Step-by-step explanation:
5 + 2² - 3(2) = 3
Is 15÷2345= 0.0063965......
Answer:
14 divided by 4139 is 0.0033824595312878
Step-by-step explanation: